Reformulating Cookies with Colored Whole Wheat Flours and Xylitol: Implications for Technological Quality, Phenolic Content, and Glycemic Response - Midik, Fazilet; Ozkan, Kubra; Karataylioglu, Lale; Ozer, Cagla; P. Shamanin, Vladimir; Pototskaya, Inna, V; Morgounov, Alexey I.; Sagdic, Osman; Koksel, Hamit (MDPI, 2026)
This study investigated the effects of incorporating colored wheat flours (red, blue, purple, and black) and replacing sucrose with xylitol on the technological, functional, and nutritional properties of cookies. Cookies were produced using 50:50 blends of colored whole wheat flours and refined cookie flour, and their physical, color, textural, phenolic, antioxidant, and in vitro glycemic index (GI) properties were evaluated. It has been determined that the addition of colored wheat flours significantly alters the textural properties. The incorporation of colored wheat flours significantly decreased width and increased thickness compared with the control cookies. The spread ratio of sucrose-containing cookies was higher (5.07 to 5.82) compared to xylitol-containing ones (4.91 to 5.41). Substitution of sucrose with xylitol generally reduced dough hardness. The colored wheat flour cookies had lower lightness values (52.31 to 63.18) compared to control samples (68.38 and 69.07 for sucrose and xylitol), while xylitol-based formulations produced slightly lighter cookies due to their lower browning potential. The cookies containing colored whole wheat flours exhibited higher hardness and brittleness than control cookies, likely due to their higher dietary fiber content, whereas xylitol resulted in softer cookies than sucrose. Cookies prepared with colored wheats showed significantly higher total phenolic content (367.41 and 424.87 mg GAE/100 g) and antioxidant capacity than the control samples (312.42 and 306.28 mg GAE/100 g for sucrose and xylitol), with purple wheat cookies exhibiting the highest values (424.69 and 424.87 mg GAE/100 g for sucrose and xylitol). Furthermore, colored wheat cookies demonstrated lower estimated GI values compared with control cookies (73.74 and 67.12), particularly those produced with blue wheat (66.68 and 60.94). Overall, the results indicate that colored wheat flours combined with alternative sweeteners such as xylitol can be used to develop cookies with improved antioxidant properties and moderated glycemic response while maintaining acceptable technological quality.
Keywords: colored wheat; cookie; texture; glycemic index; phenolic compounds; antioxidant capacity; STARCH; DOUGH; BLUE; Food Science & Technology